Striped marlin in their Pacific Ocean milieu: Vertical movements and habitats vary with time and place - Lam, Chi Hin; Tam, Clayward; Lutcavage, Molly E. (Frontiers in Marine Science, 2022)
Striped marlin, Kajikia audax, a top bycatch of the longline fishery, has been designated as being in overfished condition in the Western and Central North Pacific, and overfishing is still occurring. This prompts an urgent need to devise conservation and management measures based on the best, current information on the biology and ecology of this species. Despite decades of conventional tagging around the Hawaiian waters, ecological research on striped marlin in the Central North Pacific has been lacking since 2005, and little is known about striped marlin’s vertical habitat, diving behavior and bycatch vulnerability in this area. To address this knowledge void, 31 popup satellite archival tags (4 X-Tags; Microwave Telemetry, Inc. and 27 MiniPATs; Wildlife Computers Inc.) were deployed on striped marlin (138-192 cm eye fork length) between 2016 and 2019 via the Hawaii-based longline fleet. Transmitted time series records revealed striped marlin spent 38 and 81% of their day and night in the top 5 m, with median daytime and night depths of 44 m and 2 m, respectively. Temperatures experienced were 23.3°C, daytime median, and 24.6°C, nighttime median, to a minimum of 7.6°C at the deepest depth logged, 472 m. Striped marlin exhibited distinct swimming behaviors, including diel depth distributions, excursions around the top of the thermocline, and extended time at the surface, most likely reflecting the dynamic biophysical environment and intrinsic life history of this highly migratory predator. High post-release survivorship (86%) in tagged striped marlin, and their predominant use of the sea surface and mixed layer indicate that live release measures can be a viable bycatch reduction strategy.